ANALYSIS OF SPECIFIC CHARACTERISTICS OF WOMEN’S SPEECH IN ENGLISH AND UZBEK - Azamatov Malika Maqsud qizi; G. I. Narmurodova PhD. (Bright Mind Publishing, 2025)
This article analyzes sociolinguistically Uzbek and the specific features of English women’s speech, and it researches the functions and differences of units in women’s speech from a practical aspect.
Keywords: Sociolinguistics, linguistics, society, sociology, speech, normativity, criteria of territoriality.